Indonesian Learning Media: Setting, Making, Searching, Select-ing, Quality checklists and procedures, and Data Analysis and Synthesis - Ghufron, Syamsul; Markub, Markub; Tudy, Ida Gauran (Journal of Nonformal Education, 2023)
Online learning during the pandemic has an impact on the development of the use of learning media. This study aims to describe the Indonesian language learning media in elementary schools. This research is classified as a systematic literature review with the following procedure: (1) setting the background and objectives, (2) making research questions, (3) searching for literature, (4) selecting criteria, (5) quality check-lists and procedures, and (6) data analysis and synthesis. The database used to search for literature is Google Scholar. Searching the data using the keywords "Indonesian language learning and learning media in elementary schools". After that, screening was carried out to get scientific articles for 2017-2022 that discussed Indonesian language learning media in elementary schools. The search results totaled 54 articles were analyzed and synthesized. The analytical technique used is the narrative method by grouping the extracted data. The results showed that the most research articles were reviewed in terms of the year of publication, the design, the research subject, the object of research, the type of media in a row is 2020 by 39%, research development is 39%, the subject of 5th grade elementary school students is 22%, the object of learning Indonesian language in general amounted to 43%, the types of media used were story books and audio-visuals as much as 22% and 13%, respectively. The results of this study are very useful for teachers to make or choose the right learning media in learning Indonesian.